Espaces de bonheur dans le voyage mirbellien - Bermúdez Medina, Lola (Verbum – Analecta Neolatina, 2006)
Certain passages in OctaveMirbeau’s novels tend to subdue the imprecatory character of his fiction. This paper addresses what is referred to as espaces de bonheur ’spaces of joy’ in La 628-E8 (1907), a personal account of Mirbeau’s travels through Belgium, Germany and the Netherlands, which displays a number of characteristically modern features - a hybrid journal, travelogue and "self-fiction" - and in which three spaces are explored that please and relieve the author’s sensitivity and writing: the automobile itself, the harbour, and art, embodiments of genius, grace, and human effort.